Client Rendering Method for Desktop Virtualization Services. Issue 2 (1st April 2013) - Jang, Su Min; Choi, Won Hyuk; Kim, Won Young
Abstract : Cloud computing has recently become a significant technology trend in the IT field. Among the related technologies, desktop virtualization has been applied to various commercial applications since it provides many advantages, such as lower maintenance and operation costs and higher utilization. However, the existing solutions offer a very limited performance for 3D graphics applications. Therefore, we propose a novel method in which rendering commands are not executed at the host server but rather are delivered to the client through the network and are executed by the client's graphics device. This method prominently reduces server overhead and makes it possible to provide a stable service at low cost. The results of various experiments prove that the proposed method outperforms all existing solutions.